PTEN Inhibition Protects Against Experimental Intracerebral Hemorrhage-Induced Brain Injury Through PTEN/E2F1/β-Catenin Pathway - Zhao, Dan; Qin, Xing-Ping; Chen, Song-Feng; Liao, Xin-Yu; Cheng, Jing; Liu, Rui; Lei, Yang; Zhang, Zhi-Feng; Wan, Qi (Frontiers in Molecular Neuroscience, 2019)
Intracerebral hemorrhage (ICH) is a subtype of stroke with highest mortality and morbidity. We have previously demonstrated that bpV[pic] inhibits PTEN and activates ERK 1/2 respectively. In this study, we examined the effect of bpV[pic] in the rat ICH model in vivo and the hemin-induced injury model in rat cortical cultures. The rat model of ICH was created by injecting autologous blood into the striatum and bpV[pic] was intraperitoneally injected. The effects of bpV[pic] were evaluated by neurological tests, Fluoro-Jade C (FJC) staining and Nissl staining. We demonstrate that bpV[pic] attenuates ICH-induced brain injury in vivo and hemin-induced neuron injury in vitro. The expression of E2F1 was increased but β-catenin expression was decreased after ICH, and the altered expression of E2F1 and β-catenin after ICH was blocked by bpV[pic] treatment. Our results further show that bpV[pic] increases β-catenin expression through down-regulating E2F1 in cortical neurons, and prevents hemin-induced neuronal damage through E2F1 down-regulation and subsequent up-regulation of β-catenin. By testing the effect of PTEN-siRNA, PTEN cDNA or combined use of ERK 1/2 inhibitor and bpV[pic] in cultured cortical neurons after hemin-induced injury, we provide evidence suggesting that PTEN inhibition by bpV[pic] confers neuroprotection through E2F1 and β-catenin pathway, but the neuroprotective role of ERK 1/2 activation by bpV[pic] cannot be excluded.